Leishmania: role of P glycoprotein in drug resistance and reversion strategies. - Osorio, Edison J.; Robledo, Sara M.; Arango, Gabriel J.; Muskus, Carlos E. (Biomedica, 2005)
Protozoan parasites are important causative agents of morbidity and mortality throughout the world–a problem further complicated by the emergence of drug resistance in these parasites. Mechanisms of drug resistance include the following: decreased uptake of the drug into the cell, loss of drug activation, alterations in the drug target, and over-expression of a well-known multiple drug transporter proteins. In this review, two critical components of resistance are stressed: (1) the role of ATP binding cassette proteins, such as P-glycoproteins, in mediating drug resistance in Leishmania and other protozoans, followed by development of cross-resistance to many structurally and functionally unrelated drugs, and (2) some concepts concerning the reversal mechanism of multidrug resistance by drugs and natural products. Several modulators or chemosensitizers alter the capacity of P-glycoproteins to maintain subtoxic intracellular drug concentrations. Calcium channel blockers such as verapamil act in this mode; however, high concentrations are required for an efficient and effective inhibition and, in addition, produce undesirable side effects. The discovery of new, natural product modulators of P-glycoproteins is stressed. This category of modulators offer potentially improved efficacy and lowered toxicity for the mammalian host.